2016
DOI: 10.1097/j.pain.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of cross-over clinical trials of analgesic treatments for chronic pain: Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks systematic review and recommendations

Abstract: Cross-over trials are typically more efficient than parallel group trials in that the sample size required to yield a desired power is substantially smaller. It is important, however, to consider some issues specific to cross-over trials when designing and reporting them, and when evaluating the published results of such trials. This systematic review evaluated the quality of reporting and its evolution over time in articles of cross-over clinical trials of pharmacologic treatments for chronic pain published b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Gewandter and colleagues investigated 124 crossover clinical trials of drug treatments for chronic pain published between 1993 and 2013. They found that 28% (35/124) of trials reported baseline and post washout pain levels, and only 31% (23/75) reported a sample size calculation that specifically indicated that it was based on within participant variability 27. Straube and colleagues considered 98 crossover trials on chronic painful conditions published between 1990 and 2014 and indexed on PubMed.…”
Section: What Is the Quality Of Reporting Of Randomised Crossover Trimentioning
confidence: 99%
“…Gewandter and colleagues investigated 124 crossover clinical trials of drug treatments for chronic pain published between 1993 and 2013. They found that 28% (35/124) of trials reported baseline and post washout pain levels, and only 31% (23/75) reported a sample size calculation that specifically indicated that it was based on within participant variability 27. Straube and colleagues considered 98 crossover trials on chronic painful conditions published between 1990 and 2014 and indexed on PubMed.…”
Section: What Is the Quality Of Reporting Of Randomised Crossover Trimentioning
confidence: 99%
“… 105 A pain-specific supplement to CONSORT is also available from Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks (ACTTION), 52 as well as a discussion of issues that arise in the reporting of crossover trials. 54 A guideline for describing complex interventions in clinical trial reports has been published. 66 Additional recommendations for the reporting of SCS trials for pain are provided in Tables 3 and 4 .…”
Section: Data Analysis Interpretation and Reportingmentioning
confidence: 99%
“…Cross-over designs can be used to reduce sample size requirements when studying pain conditions that are expected to remain stable throughout the trial duration and treatments that have relatively fast onset and offset of their pharmacodynamic effects. 26 , 40 , 94 However, cross-over trials also have several potential limitations, including carry-over effects, in which the effect of an active treatment in the first period may carry over to a placebo condition in the next period and reduce the second period treatment-placebo difference. Various methods for addressing these effects have been proposed, but the best approach is to design the trial to minimize potential carry-over effects and any other causes of treatment-by-period interaction.…”
Section: “Always In Motion Is the Future”: Emerging Evidence-basedmentioning
confidence: 99%